WOMEN’S EXPERIENCES OF LIVING WITH A NARCISSIT: A MIXED METHODS APPROACH - RACHITA KANWAR,; DR. SAKSHI KAUL, (The Bioscan, 2025)
The research is a mixed method research where in the researcher is exploring women’s experiences with their narcissistic partners through a qualitative framework by interviewing and analysing the 14 case studies that focus on understanding the quality of the relationship , their self-esteem and the experience of the women, data has been collected using semi structured interviews of the narcissist's women partners to explore their relationship experience with a narcissist man .The quantitative aspect focusses on understanding the relationship satisfaction and its effects on the self-esteem of the women. The participants are age is between 25 – 35 years old, and have been in a relationship with the narcissistic man for about few years. The analysis is done using the framework of thematic analysis using QD Miner Lite software. The result of study confirm that there are concerns of commitment and women described the uncertainty and lack of long-term relationship commitment from the narcissistic partner’s end. The research concurs with the findings of Trauma bonding and Feminist theory contributing to the body of the literature confirming that the partners of the narcissist men experience low relationship satisfaction, self-doubt and dark experiences while staying in the relationship with the narcissist partner.